Islam, Tradition and Modernity in the Work of Two Somali Writers: Nuruddin Farah and Ayaan Hirsi Ali. Issue 2 (2nd July 2016) - Pucherova, Dobrota
Abstract : This article compares the representation of Somali Islamic culture in the work of two contemporary diasporic Somali intellectuals: the novelist Nuruddin Farah and the politician, philosopher and activist Ayaan Hirsi Ali. Farah's novels and Ali's autobiographical and philosophical writings both fall into the category of 'engaged literature', seeking a positive change for their troubled country. While both are critical of gender relations in Islam and express liberal and feminist views, their attitudes to Islam have different nuances and work at different levels. The article shows that despite their differences, both Ali and Farah embrace the values of liberal humanism, replacing the pious Muslim believer with the doubting and questioning Enlightenment individual, posing a challenge to the traditional Muslim identity. The difficult question that both seek to answer is how Islam can be modernized to fit the needs of contemporary Somalia and whether Enlightenment's secular values – especially the idea of the self as the ethical source – can or should replace the Islamic ethics centred around Allah.